2009
DOI: 10.1017/s0263574708004773
|View full text |Cite
|
Sign up to set email alerts
|

Smart wheelchair perception using odometry, ultrasound sensors, and camera

Abstract: SUMMARYThis paper deals with the perception mode of smart wheelchairs. First we evoke the many mobility aid prototypes developed in rehabilitation robotics by considering the point of view of perception. Then we describe the localization mode of the VAHM**. We show how the odometric, ultrasound, and vision sensors are used in a complementary way in order to locate the wheelchair in its known environment. The mode of adjustment of the odometric position by the least-squared method using ultrasonic measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Ultrasonics were used because they are tough and uncomplicated [4,5,28,29]. Sanders et al presented the most recent ultra-sonic sensor system for a wheelchair [10][11][12][13].…”
Section: Ultrasonic Sensorsmentioning
confidence: 99%
“…Ultrasonics were used because they are tough and uncomplicated [4,5,28,29]. Sanders et al presented the most recent ultra-sonic sensor system for a wheelchair [10][11][12][13].…”
Section: Ultrasonic Sensorsmentioning
confidence: 99%
“…Smart wheelchairs usually use sonar, infrared sensors, etc., to detect obstacles in the surrounding environment for enhancing safety and supporting autonomous navigation [1]. Some researchers employ computer vision techniques to visually detect obstacles or landmarks to assist in navigation [5].…”
Section: A Smart Wheelchairsmentioning
confidence: 99%
“…Satoh and Sakaue (Satoh and Sakaue, 2007) presented an omni-directional stereo vision-based IW which detects both the potential hazards in a moving environment and the postures and gestures of a user, using a stereo omni-directional system, which is capable of acquiring omni-directional color image sequences and range data simultaneously in real time. In 2008 John Spletzer studied the performance of LIDAR based localization for docking an IW system (Spletzer et al, 2008) and in 2009 Horn and Kreutner (Horn and Kreutner, 2009) showed how the odometric, ultrasound, and vision sensors are used in a complementary way in order to locate the wheelchair in a known environment. In fact, the research on IW has suffered a lot of developments in the last few years.…”
Section: Intelligent Wheelchairsmentioning
confidence: 99%